ANALISIS BUDAYA ORGANISASI MENGGUNAKAN ORGANIZATIONAL CULTURE ASSESSMNET INSTRUMENT (OCAI) PADA PT BANDENG JUWANA ELRINA - Bukhori, Ahmad; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2015)
Rigorous competition in the era of globalization becomes a challenge and a stimulant for every company to undertake changes continously. As a result, companies are able to develop and to preserve their existence. PT Bandeng Juwana Elrina is one of manufacturers which produces processed food called bandeng. This company is doing inexorably improvements and developments. Nonetheless, in the development process, the company has not analyzed yet systematic cultural analyzes. It can be the guidance for the company in the development process and the improvement process. Therefore, this research makes a mapping of organizational culture. This research is intended to analyze the organizational culture profile. Then the result can be an advice for the company in formulating an accurate organizational culture. This research has been conducted by using OCAI ( Organizational Culture Assesment Instrument) method. This research surveyed the Board of Director, the General Manager, the department manager and the department head. Through descriptive quantitative approach, this research would be expected being able to reveal and to analyze the cultural profile of PT Bandeng Juwana Elrina. The result of this research shows that there are differences in cultural perception among the Board of Director and the three lower positions. There are the General Manager, the department manager and the department head. They argue that the current dominant culture is clan. In contrast, the Board of Director points out that the recent dominant culture is adhocracy. On the other hand, these four positions also have different perceptions in the organizational culture profile which will be expected in the future. The Board of Director expects that it will be a combination of clan culture and adhocracy. The General Manager and the department head hope that it will be an adhocracy culture. The portrait of current culture are the dominancy of clan culture and the different perception among position stages. The different perception is in the expectation of organizational culture in the future time. It tends to dirrect at clan culture and adhocracy. These can be the consideration for the company to formulate the culture which is appropriate with the company’s vision and mision.